Delusional thinking in violent offending: implications for risk assessment and treatment - Hepburn, Eve E. (2016)
The impact of delusional thinking on the violent behaviour of individuals with psychiatric diagnoses has been explored using a variety of investigative methods. The notion that delusions play a role in an individual’s violent offending has been broadly upheld within the work of this thesis. The nature or function of delusions in this process appears to be affected by a range of mediating and moderating factors. The complexity of these was illustrated during the conduction of a case study.